(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The research indicates the importance of the serving skill, as it is a basic skill through which one can start playing and score a lot of points in matches. The more effective the serve is, the more points it will achieve, and this is clearly demonstrated by the participation of the research sample in the Iraqi Universities Championship for the season (2022-2023). The study also showed the importance of using modern laboratory equipment (Biosyn system) in detecting the values of angular kinetic variables and their effective impact in training and benefiting from them in skill development. It also aimed to identify the characteristics of angular kinetics and the extent of their impact on implementing the skill effectively, which makes the process of motor development or learning more effective and positive. Using these digital values in the training process has many benefits and functions, the most important of which is determining the correct motor paths and other important benefits that work to achieve the greatest possible training and educational efficiency. In addition to saving the effort and time spent on the training unit, the researcher used the descriptive approach and identified the research population, which is the Al-Qadisiya University volleyball team participating in the Iraqi Universities Championship for the season (2022-2023), and chose a sample of 4 players who perform the aces only. As for the most important conclusions, the results showed the importance of providing information about the chain of moments during the performance in the main stage (the moment the ball is hit) and then benefiting from it in interpreting the movement. The results of the characteristics of the angular kinetic curve for the variables of the moment series showed a consistent shape in the main stage (hitting the ball) with the skill of serving the volleyball to the parts of the body, each according to the amount of its mass and its contribution to the hitting stage.